Impact of professional development activities on teachers’ formative assessment practices - Lam, Le; Lien, Vu Phuong; Hung, Le Thai; Vy, Nguyen Thi Phuong (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to explore the impact of professional development (PD) activities on the practice of formative assessment, mediated by outcome expectancy and self-efficacy. The study used a survey method to unveil compelling insights among 5,546 primary teachers within the context of Vietnam. The findings from partial least squares structural equation modeling (PLS-SEM) demonstrated a significant impact of PD on teachers’ outcome expectancy regarding formative assessment and their self-efficacy in practicing it. The study emphasizes that PD significantly enhances the effectiveness of practice when interconnected with outcome expectancy and self-efficacy. When teachers anticipate positive outcomes and possess strong self-belief, PD notably improves their classroom formative assessment practices. These findings underscore the importance of tailoring PD initiatives to bolster teachers’ outcome expectancy and self-efficacy. By emphasizing these aspects, PD can significantly elevate its positive influence on classroom practices, especially in formative assessment. This study provides crucial insights for educational policymakers and institutions aiming to maximize the impact of PD programs for primary educators in Vietnam.